Sukuk Negara as an Alternative for APBN Financing in Indonesia - Riswan Riswan; Andi Rustam; Linda Arisanty Razak; Muchriana Muchran (Penerbit Goodwood, 2023)
Purpose: In supporting APBN financing, the government always prioritizes non-debt financing. However, the government also uses debt financing to meet the financing needs of the state budget. One of the alternative efforts that must be made by the Government is to develop Sharia-based SBN or what can be called Sukuk Negara. Method: This research uses a qualitative methodology. Result: Based on the results of research that has been conducted, it is known that State Sukuk have a major role in driving the growth of Islamic finance in Indonesia and can reduce the financing of the state budget deficit.